Determinants of provincial financial accountability in Indonesia: The moderating role of information and communication technology - Antoni, Syafrul; Rahayu, Sri; Friyani, Rita; Lestari, Wira (Badan Pemeriksa Keuangan Republik Indonesia, 2026)
Accountability is a cornerstone of good governance, particularly in the era of fiscal decentralization. Despite ongoing reforms, many Indonesian provinces continue to face challenges related to limited transparency, heavy reliance on central government transfers, and inadequate technological capacity. This study examines the determinants of provincial financial accountability by assessing the influence of e-government, local government size, and financial dependence, while incorporating information and communication technology (ICT) as a moderating variable. Using unbalanced panel data from 31 provinces over the 2019–2023 period (155 observations), the results show that e-government has a positive and significant effect on financial accountability, whereas local government size and financial dependence exert significant negative effects. ICT moderates these relationships asymmetrically by weakening the positive impact of e-government, strengthening the negative impact of local government size, and showing no significant moderating effect on financial dependence. These findings suggest that digital transformation alone is insufficient to improve accountability without adequate institutional capacity and governance quality. Practically, local governments should prioritize the integration of interoperable, data-driven e-government systems and strengthen digital human resource capacity, while the central government should enhance system interoperability, promote performance-based fiscal transfers, and expand financial transparency.